Dual antitumour effect of 5-azacytidine by inducing a breakdown of resistance-mediating factors and epigenetic modulation. Issue 2 (23rd November 2010) - Venturelli, Sascha; Berger, Alexander; Weiland, Timo; Zimmermann, Martina; Häcker, Sabine; Peter, Christoph; Wesselborg, Sebastian; Königsrainer, Alfred; Weiss, Thomas S; Gregor, Michael; Fulda, Simone; Lauer, Ulrich M; et al.
Abstract : Background: The cytokine tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) has shown promising anticancer activity in early clinical settings by selectively inducing apoptosis in different tumour types. However, some tumour entities such as hepatocellular carcinoma (HCC) display an inherent resistance to TRAIL. A huge effort has been made to unravel strategies for a clinically applicable sensitisation of resistant cancer cells to TRAIL. Reversible epigenetic alterations such as DNA methylation play a major role in development, maintenance and resistance phenomena of tumour cells. Currently, several clinical trials are exploiting the potential of epigenetic drugs, such as 5-azacytidine (5-aza-CR) or 5-aza-2′-deoxycytidine (5-aza-dC) to break primary or secondary resistance phenomena of cancer cells. Therefore, 5-aza-CR and 5-aza-dC were investigated in the context of TRAIL resistance. Methods: Alterations in proliferation, apoptosis, regulatory proteins and toxicity were investigated in TRAIL-resistant hepatoma, and also in renal, colon and pancreatic cancer cells as well as non-transformed human-derived primary hepatocytes, tissue slices isolated from human liver and non-malignant colon cells, all of which had been exposed to demethylating drugs and/or TRAIL. Results: Within hours, 5-aza-CR but not 5-aza-dC sensitised in vitro cultured tumour cells to TRAIL, first by activating caspases, followed by a subsequent induction of apoptosis. This surprisingly rapid sensitisation was confirmed in vivo employing a chorioallantoic membrane assay. As a major mechanism, a 5-aza-CR-induced inhibition of cellular protein synthesis was found which led to a breakdown of tumour-protecting factors such as the antiapoptotic factor FLICE inhibitory protein (FLIP). Importantly, TRAIL and 5-aza-CR did not induce relevant toxicity or apoptosis in primary hepatocytes, liver slices from different human donors and in normal colon cells. Conclusions: Molecular evidence is provided for a novel 5-aza-CR-based translational approach enabling a twofold treatment of apoptosis-resistant tumour entities, not only by an epigenetic reversion of the malignancy-associated phenotype but also by an efficient resensitisation to apoptosis-inducing substances such as TRAIL.